Design and implementation of a framework for persistent identification and communication in emerging networks - Joud Khoury; Henry Jerez; Luca De Cicco (Proceedings of the 4th International Conference on Testbeds and Research Infrastructures for the Development of Networks & Communities, 2008)
The Internet Protocol (IP) is currently used to provide inter-networking among heterogeneous access networks. However, the evolution of and the innovation within these networks is greatly hindered by the geographical and topological rigidness of the protocol implementation that hinders the support for flexible unstructured communication paradigms. To broaden the user’s innovation space and to efficiently embrace the characteristics of these emerging unstructured networks, clean-slate architectural approaches are being pursued. In this paper, we present the Persistent Identification and NeTworking research framework (PINT); an implementation of the Transient Network Architecture (TNA) currently being developed between the University of New Mexico and the Corporation for National Research Initiatives. PINT provides the research community with a modular and extensible set of networking components and primitives that enable novel research and experimentation atop a persistently identified networking platform. This technology provides a ground for inter-networking of heterogeneous communication networks where novel networking primitives are exposed through the Persistent Identification and Networking Layer (PINL), allowing mobile and stationary entities to communicate securely based on persistent identifiers that are location independent.
Keywords: mobility; persistent identification; testbed